Analysis of the Impacts and Management Strategies of Plastic Waste Pollution on the Sustainability of the Marine Ecosystem in Ambon Bay from an Islamic Perspective - Mesenu, Mesenu; Syamson, Indra; Martia Rahmani, Ratih; Harisjon, Harisjon (Council: Education Journal of Social Studies, 2026)
Plastic pollution in Ambon Bay poses a serious threat to the sustainability of marine ecosystems and the well-being of coastal communities. This study aims to analyze the ecological, social, and economic impacts of plastic waste accumulation and to evaluate effective management and mitigation strategies. Using a descriptive–qualitative method through literature review and regional data analysis, the findings show that increasing plastic production and weak waste management systems have led to ecosystem degradation, including coral reef damage, declining biodiversity, and reduced income for local fishers. From an Islamic perspective, environmental preservation is a mandate entrusted to humans as khalifah on earth; thus, marine pollution is considered a form of fasad (destruction) that violates the principle of natural balance. Therefore, waste management requires collaboration among the government, industry, and the community, grounded in the values of maslahah (public benefit), amanah (responsibility), and ihsan (excellence), to achieve the goals of maqasid shariah in ensuring equitable and sustainable environmental stewardship